A study of indoor radio coverage using antenna and leaky feeder - Jiang, Quansheng (2008)
Focuses on the comparative study of indoor radio coverage using antenna and leaky feeder approaches. We develop indoor radio propagation model using the ray-tracing technique & use the model to predict indoor radio coverage using an antenna as its transmitting antennas.